Acute stroke thrombolysis: time to dispense with the clock and move to tissue-based decision making?. (April 2011) - Bivard, Andrew; Spratt, Neil; Levi, Christopher R; Parsons, Mark W
Currently, imaging is predominantly used to exclude patients for thrombolysis, rather than identify patients most likely to benefit. This means that patients are being selected for treatment without reference to tissue pathophysiology. Imaging of specific stroke pathophysiology may be the key to selecting patients most likely to benefit from thrombolysis, and could revolutionize acute stroke assessment and treatment. The technology is available to identify the acute infarct core and possibly the penumbra, via magnetic resonance diffusion-weighted imaging, and both magnetic resonance- and computed tomography-perfusion imaging techniques. However, these modalities require fine tuning before they can be reliably implemented in a routine clinical setting.